Echinocystic Acid Isolated from Eclipta prostrata Suppresses Lipopolysaccharide-Induced iNOS, TNF-α, and IL-6 Expressions via NF-κB Inactivation in RAW 264.7 Macrophages - Ryu, Suran; Shin, Ji-Sun; Jung, Ji Yun; Cho, Young-Wuk; Kim, Su Jung; Jang, Dae Sik; Lee, Kyung-Tae (Planta Medica, 2013)
In this study, we aimed to identify the compounds in Eclipta prostrata responsible for its anti-inflammatory effects using an in vitro bioassay. Three triterpenoids, eclalbasaponin I, eclalbasaponin II, and echinocystic acid, were isolated from an EtOAc fraction of the 70 % EtOH extract of E. prostrata by activity-guided fractionation based on the inhibition of nitric oxide release from lipopolysaccharide-induced RAW 264.7 macrophages. Of these three triterpenoids, echinocystic acid inhibited lipopolysaccharide-induced production of nitric oxide and cytokines such as tumor necrosis factor-α and interleukin-6. Consistent with these observations, echinocystic acid concentration-dependently inhibited lipopolysaccharide-induced inducible nitric oxide synthase expression at the protein level and inducible nitric oxide synthase, tumor necrosis factor-α, and interleukin-6 expression at the mRNA level, and inhibited lipopolysaccharide-induced iNOS promoter binding activity. In addition, echinocystic acid suppressed the lipopolysaccharide-induced transcriptional activity of nuclear factor-κB by blocking the nuclear translocation of p65.
Keywords: Eclipta prostrata; Asteraceae; echinocystic acid-nitric oxide; inducible nitric oxide synthase; nuclear factor-κB